Epilepsy Unveiled: Advances in Understanding, Diagnosis, and Management - Shrijita Sikdar,; Udita Dutta,; Ayan Ghosh,; Suparna Mondal,; Krisnendu Das, (Indian Journal of Pharmacy & Drug Studies, 2024)
In addition to the numerous stress that characterize individuals today's fast-paced lives, the majority of people on the planet encounter various neurological problems. Epilepsy, one of the most common neurological disorders of the brain, affects over 50 million people worldwide. 90% of whom are from developing nations. Genetic factors, brain infections, strokes, tumors, and high body temperatures are all contributors to epilepsy. Along with the social stigma that brings discrimination against patients and even their families in the community, it also, creates a significant financial burden on the healthcare systems of different countries. People with epilepsy frequently experience extreme mental suffering, behavioral problems, and little to no social engagement. Numerous seizure types exist, as are numerous mechanisms by which the brain can trigger seizures. Neuronal hyperexcitability and neural circuit hypersynchrony are the two fundamental features of seizure genesis. Numerous mechanisms may disturb the equilibrium between excitation and inhibition, predisposing a specific or generalized region of the brain to hyperexcitability and hypersynchrony. The review will include the classification, background, epidemiology, etiology, pathophysiology, symptoms, diagnosis, and management of epilepsy.